Adopting Omnichannel Strategies for Enhanced Customer Experience in E-Business - Rahman, Arif; Hayya, Lidya Nur; Indah P, Euis Ayu; Redjeki, Finny (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The rapid advancement of digital technologies has reshaped consumer behavior and expectations in the realm of e-business. Customers today seek seamless and consistent experiences across various channels—online and offline. Omnichannel strategies have emerged as a comprehensive approach that integrates these channels to provide a unified and personalized customer experience. This paper explores the adoption of omnichannel strategies and their impact on enhancing customer experience in e-business.This study uses a qualitative-descriptive method with literature review and case analysis as its basis. Data were collected from previous research, white papers, and official industry reports from sectors such as retail, banking, and service industries. The framework of analysis focuses on three key dimensions of customer experience: consistency, personalization, and convenience.Findings suggest that adopting an omnichannel strategy significantly improves customer satisfaction, engagement, and loyalty. When businesses integrate digital and physical touchpoints—such as websites, mobile apps, chatbots, social media, and in-store experiences—customers feel more connected and valued. Brands like Sephora, IKEA, and Amazon have successfully implemented omnichannel models that deliver real-time, personalized experiences to customers at every stage of their journey.However, implementing omnichannel strategies requires high investment in data infrastructure, customer journey mapping, and cross-functional coordination.